PELATIHAN K3 BAGI TENAGA KERJA DI SEKTOR PERTANIAN DAN PETERNAKAN DI DESA WARNASARI, PANGALENGAN KABUPATEN BANDUNG JAWA BARAT - Damiri, Ahmad; Djatmiko, Teguh; Sulaeman, Iman; Susbiyantoro, Susbiyantoro; Firlana, Mira (POLITEKNIK LP3I JAKARTA, 2025)
Occupational Safety and Health (OSH) is a crucial aspect in supporting productivity and work sustainability, especially in the agriculture and livestock sectors, which carry a high risk of work-related accidents and occupational diseases. This community service activity aims to enhance the understanding and awareness of workers in the agriculture and livestock sectors regarding the importance of applying OSH principles in their daily activities. The activity was carried out on June 13 and 14, 2025, in the 3rd-grade classroom of Palayangan State elementary school, Warnasari Village, Pangalengan Sub-district, Bandung Regency, with a total of 25 participants consisting of vegetable farmers and livestock breeders. The methods used in this training included interactive lectures, group discussions, simulations on the use of personal protective equipment (PPE), and pre-test and post-test evaluations. The results of the activity showed an increase in participants' understanding of basic OSH concepts and their motivation to apply them in their respective businesses. This activity is expected to be an initial step in creating a safer and healthier work culture within the village community.